The four seasons of marriage: - Chapman, Gary D., 1938- (Tyndale Audio, 2005)
Presents an easy-to-grasp framework to help couples understand their marriage and seven practical strategies for strengthening or improving their marriage relationship. A valuable resource for couples regardless of how long they've been married, this biblically based book is a reference tool to help couples through every season of marriage.